Bioecological analysis of fi sh production off the northern and eastern coasts of Rio Grande do Norte State - da Silva, Alessandra Cristina; Filho, Antônio Adauto Fonteles (Arquivos de Ciências do Mar, 2009)
The marine fi shing fl eet of Rio Grande do Norte State is made up mostly of artisanal craft which account for 85% of its total numbers, and gillnet and hand-and-line are the most productive fi shing gear. This research work was designed with the aim of analyzing the bioecology of the fi shing activity and its catch on the northern and eastern sectors of the state’s coast. The data were obtained as the outcome of the ESTATPESCA Project run by the regional research offi ce of IBAMA, during the period from January to December, 2005, and consisted of statistical information on yield, fi shing effort and species abundance. The data analysis dealt with explaining variations on the fi sh fauna distribution by means of species diversity and ecological indices, and by the interaction of the production patterns during rainy and dry seasons. The results showed that the highest yields, the lowest values of species diversity and richness, and a higher species dominance occurred during the rainy season, having the fi shery “boat with hand-and-line/scoop net” as the most productive one, and the fl ying fi sh and dolphin fi sh as the most abundant species. On the eastern coastline, the dry season stood out as concerns the relevance of the “boat and hand-and-line” fi shery, and abundance of the Atlantic tuna among the caught fi sh.